171 Nippv Does not Reduce Bronchopulmonary Dysplasia (Bpd) or Death in Extremely Low Birth Weight Infants - A Randomised Trial. (October 2012) - Millar, D; Kirpalani, H; Lemyre, B; Yoder, BA; Chiu, A; Roberts, R
Abstract : Background: Standard care of preterm infants includes nCPAP & NIPPV. We compared rates of BPD or death in a randomised trial of NIPPV or nCPAP. Methods: Eligible infants were preterm, birth weight < 1000g; requiring either (i) non-invasive respiratory support within first seven days, "no intubation/early extubation group", or (ii) were < 28 days at first extubation - "prior intubation". Central block randomisation to NIPPV or nCPAP was conducted via the web. Primary outcome was a composite of death (prior to 36 weeks' gestational age [GA]) or BPD at 36 weeks' GA: defined as requiring ventilation; FiO2 > 30%; or positive oxygen reduction test (ORT). Sample size 1000 (β 80%; 2-tailed α 5%) to demonstrate 20% reduction in primary outcome. Results: 36 international sites enrolled 1007 infants. Observed rates of BPD or death were similar in the two groups. BPD outcome, in the 21 infants with no ORT, assessed by clinical definition of oxygen at 36 weeks' GA: no alteration in treatment differences. Conclusions: In infants < 1000g NIPPV does not confer further benefit nor risk for survival free of BPD at 36 weeks' GA compared to nCPAP.